Listening to the Eritrean Migrants’ Vulnerability Voices in Ragwah Saudā` Arabic Eritrean Novel: A Postcolonial Perspective - Mahmudah Mahmudah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2026)
The study aims to demonstrate the vulnerability of Eritrean migrants in the Arabic novel Ragwah Saudā` (2018) by Eritrean writer Ḥajjī Jābir. It analyzes this phenomenon using Postcolonial Theory in relation to migration, considering that migration is a long-term consequence of European colonialism and that the new Eritrean authorities behave in a colonial manner. To operationalize this framework, the study applies the concept of vulnerability to examine the conditions Eritrean migrants face. This research employs an interpretive method, a technique of giving meaning to data that have been classified interpretively in a postcolonial perspective. The results indicate that the primary cause of Eritreans' departure from their homeland was compulsory military service imposed by the authoritarian government. Thus, Eritreans experienced vulnerability from the outset, a condition that can be described as a form of biopolitics. Eritrean migrants are also narrated as experiencing vulnerability throughout their migration journey, particularly in several locations in Ethiopia and in their destination country, Israel. This vulnerability is closely related to religious identity and otherness. Although migrants have attempted to create new narratives about themselves, they have not been able to escape the vulnerability they experience.